Bottlenecks to product rate variation problem with batching - Shree Ram Khadka (Bibechana, 2012)
The product rate variation problem with batching minimizes the variation in the rate at which different models of a common base product are produced on the assembly lines with the assumption of significant setup and arbitrary processing times for each copy of each model. Establishment of bottlenecks to the problem is important for the feasible and the optimal solution to the problem. In this paper, the lower and the upper bottlenecks to the problem are established. Moreover, small bottlenecks that lead to optimality to some instances are investigated.